17-β estradiol increases parvalbumin levels in Pvalb heterozygous mice and attenuates behavioral phenotypes with relevance to autism core symptoms - Filice, Federica (Mol Autism, 2018)
BACKGROUND: Autism spectrum disorder (ASD) is a group of neurodevelopmental disorders characterized by two core symptoms: impaired social interaction and communication, and restricted, repetitive behaviors and interests. The pathophysiology of ASD is not yet fully understood, due to a plethora of genetic and environmental risk factors that might be associated with or causal for ASD. Recent findings suggest that one putative convergent pathway for some forms of ASD might be the downregulation of the calcium-binding protein parvalbumin (PV). PV-deficient mice (PV−/−, PV+/−), as well as Shank1−/−, Shank3−/−, and VPA mice, which show behavioral deficits relevant to all human ASD core symptoms, are all characterized by lower PV expression levels. METHODS: Based on the hypothesis that PV expression might be increased by 17-β estradiol (E2), PV+/− mice were treated with E2 from postnatal days 5–15 and ASD-related behavior was tested between postnatal days 25 and 31. RESULTS: PV expression levels were significantly increased after E2 treatment and, concomitantly, sociability deficits in PV+/− mice in the direct reciprocal social interaction and the 3-chamber social approach assay, as well as repetitive behaviors, were attenuated. E2 treatment of PV+/+ mice did not increase PV levels and had detrimental effects on sociability and repetitive behavior. In PV−/− mice, E2 obviously did not affect PV levels; tested behaviors were not different from the ones in vehicle-treated PV−/− mice. CONCLUSION: Our results suggest that the E2-linked amelioration of ASD-like behaviors is specifically occurring in PV+/− mice, indicating that PV upregulation is required for the E2-mediated rescue of ASD-relevant behavioral impairments. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13229-018-0199-3) contains supplementary material, which is available to authorized users.